1991
DOI: 10.3109/00048679109064441
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Needs of Torture Survivors

Abstract: Growing recognition that the world faces a modern epidemic of torture has stimulated widespread interest amongst mental health professionals in strategies for the treatment of survivors. In this article we outline the distinctive experiences of torture survivors who present for treatment in western countries. These survivors are usually refugees who, in addition to torture, have suffered a sequence of traumatic experiences and face ongoing linguistic, occupational, financial, educational and cultural obstacles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 18 publications
0
30
0
4
Order By: Relevance
“…PE has often been criticized on the grounds that people who have difficulties tolerating distress may not be able to manage the emotional demands of PE, and therefore will not benefit from PE (for discussion, see Herman, 2001; Neuner et al, 2008; Silove, 1996; Silove, Tarn, Bowles, & Reid, 1991). These cases, often called “complex PTSD,” can be conceptualized as more severe cases of PTSD or more comorbid cases in which the patient has marked difficulties with emotion regulation, leading to strong mood swings, difficulty stabilizing emotional reactions, impulsive behaviors, self-harm, and difficulties with interpersonal relationships (Cloitre, Miranda, Stovall-McClough, & Han, 2005).…”
Section: Targeting More Treatment-resistant Populationsmentioning
confidence: 99%
“…PE has often been criticized on the grounds that people who have difficulties tolerating distress may not be able to manage the emotional demands of PE, and therefore will not benefit from PE (for discussion, see Herman, 2001; Neuner et al, 2008; Silove, 1996; Silove, Tarn, Bowles, & Reid, 1991). These cases, often called “complex PTSD,” can be conceptualized as more severe cases of PTSD or more comorbid cases in which the patient has marked difficulties with emotion regulation, leading to strong mood swings, difficulty stabilizing emotional reactions, impulsive behaviors, self-harm, and difficulties with interpersonal relationships (Cloitre, Miranda, Stovall-McClough, & Han, 2005).…”
Section: Targeting More Treatment-resistant Populationsmentioning
confidence: 99%
“…Observations following WWII suggested that psychotic-like symptoms and frank forms of psychosis were common amongst survivors of the Holocaust, although selection biases could have influenced these findings [16]. Since then, clinicians in the field of traumatic stress have argued that gross forms of human rights violations can lead to a fundamental loss of trust amongst survivors, resulting in a tendency towards suspicion and even paranoia, phenomena that are not encompassed by contemporary criteria for PTSD [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Many refugees are exposed to potentially traumatising situations during several phases of their journey: surviving war or organised violence, including imprisonment and torture; becoming fugitives; leaving their home country, often to stay in refugee camps before being granted a right to stay in a country of settlement; and experiencing the stresses of resettlement and discrimination (Silove, Tarn, Bowles, & Reid, 1991). Consequently, their chances of developing post-traumatic stress disorder (PTSD; American Psychiatric Association, 1994) are high: in western countries, refugees are 10 times more likely to have PTSD than general populations (Fazel, Wheeler, & Danesh, 2005).…”
mentioning
confidence: 99%